Gender Differences in Poverty and Household Composition through the Life-Cycle : A Global Perspective - Munoz Boudet, Ana Maria; Buitrago, Paola; De La Briere, Benedicte Leroy; Newhouse, David; Rubiano Matulevich, Eliana; Scott, Kinnon; Suarez-Becerra, Pablo (World Bank, Washington, DC, 2018)
This paper uses household surveys from 89 countries to look at gender differences in poverty in the developing world. In the absence of individual-level poverty data, the paper looks at what can we learn in terms of gender differences by looking at the available individual and household level information. The estimates are based on the same surveys and welfare measures as official World Bank poverty estimates. The paper focuses on the relationship between age, sex and poverty. And finds that, girls and women of reproductive age are more likely to live in poor households (below the international poverty line) than boys and men. It finds that 122 women between the ages of 25 and 34 live in poor households for every 100 men of the same age group. The analysis also examines the household profiles of the poor, seeking to go beyond headship definitions. Using a demographic household composition shows that nuclear family households of two married adults and children account for 41 percent of poor households, and are the most frequent household where poor women are found. Using an economic household composition classification, households with a male earner, children and a non-income earner spouse are the most frequent among the poor at 36 percent, and the more frequent household where poor women live. For individuals, as well as for households, the presence of children increases the household likelihood to be poor, and this has a specific impact on women, but does not fully explain the observed female poverty penalty.